2009
DOI: 10.4314/wajae.v8i1.45789
|View full text |Cite
|
Sign up to set email alerts
|

<i>Mucuna pruriens</i> and its effect on some physical, chemical and biological properties of a Forest Acrisol

Abstract: The effect of Mucuna pruriens, a herbaceous legume, on some properties of a forest acrisol was examined in RCBD experiment of four treatments: control, NPK fertilizer, mucuna incorporation and mucuna mulch. At flowering, the fresh biomass was cut at soil level, chopped up and applied to the soil either by incorporation or as mulch. In both cases, mucuna improved the physical, chemical and biological properties of the soil. Available soil moisture content increased from 9.54% to values between 10.20% and 11.40%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The foliage of Mucuna contributes biomass to the soil. At the same time, it is reported that the roots can fix from 201 [17] up to 331 kg of nitrogen per hectare [18], providing organic matter for soil regeneration and health [19,20]. Many studies reported the benefits of using Mucuna pruriens as a cover crop or intercrop, mainly with maize [17,21].…”
Section: Introductionmentioning
confidence: 99%
“…The foliage of Mucuna contributes biomass to the soil. At the same time, it is reported that the roots can fix from 201 [17] up to 331 kg of nitrogen per hectare [18], providing organic matter for soil regeneration and health [19,20]. Many studies reported the benefits of using Mucuna pruriens as a cover crop or intercrop, mainly with maize [17,21].…”
Section: Introductionmentioning
confidence: 99%